2015
DOI: 10.1002/jsfa.7373
|View full text |Cite
|
Sign up to set email alerts
|

In situ evaluation of the fruit and oil characteristics of the main Lebanese olive germplasm

Abstract: The findings of this study provide a first picture of the main characteristics of olives and oils currently produced in Lebanon. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
6
11
1
Order By: Relevance
“…From this, it is clear that the sterol composition of coriander vegetable oil is strongly dependent on the fruit origin. This has also been reported for other important vegetable oils, such as olive oil, where the sterol content and composition was found to be highly dependent on olive cultivar, fruit ripening, and agro-environmental conditions [37,38].…”
Section: Resultssupporting
confidence: 65%
“…From this, it is clear that the sterol composition of coriander vegetable oil is strongly dependent on the fruit origin. This has also been reported for other important vegetable oils, such as olive oil, where the sterol content and composition was found to be highly dependent on olive cultivar, fruit ripening, and agro-environmental conditions [37,38].…”
Section: Resultssupporting
confidence: 65%
“…Abu-Reidah et al 18 also reported values higher than 0.5 for this parameter in Nabali virgin olive oils from Nablus, Salfit, Qalqilya and Jenin provinces of the northern West Bank in the 2007 harvest. As well, Chehade et al 24 informed about values slightly exceeding 0.5 for Souri cultivar and exceeding 1.0 for Baladi cultivar in Lebanon. Arbequina exceeded the limit allowed by the IOC TS for several sterols included Δ-7-stigmastenol in a study on the adaptability to Argentinian climate 25 the sensory profile of the oils of the five tested Palestinian cultivars showed a low green fruity olfactory profile and a medium-intense olive fruit sensation Table 5 .…”
Section: Sterol Content and Compositionmentioning
confidence: 89%
“…Lebanon is rich in indigenous and ancient olive trees and its history of olive traditions is as old as its cultural history (3, 4). The Lebanese groves are dominated by the main traditional denomination “Baladi .” Other old varieties are still found in some ancient groves e.g., “Ayrouni,” “Sorani,” “Dal,” “Jlot,” and “Abou Chawkeh” across the country (5, 6). A few other varieties, introduced from neighboring Arab countries, are also found such as “Nabali” which is one of the oldest olive varieties in the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…Yet little attention has been given to the authentication and characterization of Lebanese olive oils. Chehade et al (6, 37) described some oil traits for eight Lebanese olive varieties; however, many other varieties cultivated in Lebanon are still not comprehensively assessed. In this manuscript, we report the characterization of monovarietal olive oils for 11 varieties cultivated in northern Lebanon for their OC, fatty acid and phenolic composition along fruit ripening with the perspective of evaluating and valorizing Lebanese olive oil.…”
Section: Introductionmentioning
confidence: 99%